ANALISIS PENGARUH VARIABILITAS IKLIM TERHADAP PENDAPATAN USAHATANI JERUK SIAM (Citrus nobilis. L) di KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU - Amanda Dwi Pratiwi; Sischa Febriani Yamesa Away; Defidelwina (SUNGKAI, 2026)
This study aims to analyze the effect of climate variability on the income of tangerine farmers in Bangun Purba District, Rokan Hulu Regency. The data used is panel data from 22 farmers over five years, the sample was determined using purposive sampling with the criteria of having produced from 2019 to 2023 and analyzed using a panel data regression model. The results showed that rainfall, duration of sunshine and air humidity significantly influence farmers' income. The best model used is REM determined through the Chow test, Hausman test, and Lagrange Multiplier test. Climate variability that is beyond the threshold limit has an impact on income, therefore appropriate adaptation strategies are needed so that farmers can reduce the negative impact of climate change on their farming.